2015
DOI: 10.1016/j.jelechem.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic activity of electrodeposited cobalt oxide films to produce oxygen gas from water

Abstract: An electrocatalytic cobalt oxide film for water oxidation was prepared on an indium tin oxide (ITO)-coated substrate by anodic electrodeposition. Atomic force microscopy measurements revealed that numerous particles with a diameter of 100-250 nm were uniformly dispersed on the ITO substrate and the particle size increased when prepared at higher temperature. Cyclic voltammograms of the Co oxide-coated ITO electrodes were measured in alkaline and neutral aqueous solutions to examine their redox characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Postprocessing or additional species can endow Co‐based electrocatalysts prepared in the electrolytes with new property or improved OER activity. Cobalt oxide film prepared on an ITO‐coated substrate by anodic electrodeposition and treated at 450 °C was used as a WOC in the neutral electrolyte containing phosphate ions . It is also found that the cobalt‐oxide related electrocatalysts can be converted from H 2 ‐evolution catalyst to O 2 ‐evolution catalyst, which could be developed as a bifunctional water splitting catalyst .…”
Section: Nonprecious Metals Based Oer Electrocatalystsmentioning
confidence: 99%
“…Postprocessing or additional species can endow Co‐based electrocatalysts prepared in the electrolytes with new property or improved OER activity. Cobalt oxide film prepared on an ITO‐coated substrate by anodic electrodeposition and treated at 450 °C was used as a WOC in the neutral electrolyte containing phosphate ions . It is also found that the cobalt‐oxide related electrocatalysts can be converted from H 2 ‐evolution catalyst to O 2 ‐evolution catalyst, which could be developed as a bifunctional water splitting catalyst .…”
Section: Nonprecious Metals Based Oer Electrocatalystsmentioning
confidence: 99%
“…[8][9][10][11] Among all electrocatalysts reported the cobalt-containing oxides have been investigated due to their high performance for the OER. [12][13][14][15][16][17][18][19][20][21][22][23] On the other hand, cobalt oxides have been used in batteries and supercapacitive applications [24][25][26] as well as gas sensors. 27 Different paths have been investigated in order to enhance the electrocatalytic activity of the Co 3 O 4 such as: the development of new morphologies, 19,28 selection of different substrates 18 and the development of composite materials which include the use of graphene.…”
mentioning
confidence: 99%